The influence of work abilities and work environment on employee performance in the seluma district regional development planning agency (bappeda) office - Venti Delvia Okmawati; Neri Susanti; Yesi Indian Ariska (Penerbit Jurnal Indonesia, 2024)
The purpose of this research is to determine the influence of work ability and work environment on employee performance at the Seluma Regency Regional Development Planning Agency (BAPPEDA) Office. This type of research is a type of quantitative descriptive research. The data collection method in this research uses observation and questionnaire techniques, with a sample of 60 respondents. The results of the research show that the multiple linear regression Y = 22.644 + 0.134 (X1) + 0.439 (X2) + 3.451. Where the coefficient is positive, meaning that there is a positive or unidirectional relationship between the work ability variable (X2) and the work environment (X1) the value is zero, then employee performance (Y) will increase by 0.439. The coefficient is positive, meaning that there is a positive or unidirectional relationship between the work environment (X2) and employee performance (Y) at the Seluma Regency Regional Development Planning Agency (BAPPEDA) office. The results of the work ability test (X1) show tcount 2.984 > ttable 1.6706 and significance 0.004 <0.05, so the results of the hypothesis Ha are accepted and Ho is rejected, meaning work ability (X1) has a positive and significant effect on employee performance (Y) in the Agency's office. Regional Development Planning (BAPPEDA) Seluma Regency. The results of the work environment test (X2) show tcount 6.638 > ttable 1.6706 and significance 0.000 <0.05, so the results of the hypothesis Ha are accepted and Ho is rejected, meaning the work environment (X2) has a positive and significant effect on employee performance (Y) in the Agency's office Regional Development Planning (BAPPEDA) Seluma Regency. The result of the Fcount value is greater than the Ftable value, namely 25.679 > 2.76, so it is concluded that the hypothesis is accepted, meaning that there is a simultaneous influence between work ability (X1) work environment (X2) on employee performance (Y) at the Regional Development Planning Agency (BAPEDA) office. Seluma Regency. This can be seen at the significance level of 0.000 <0.05.